Ecological dyeing of acrylic yarn with colorant derived from natural lac dye - VUTHIGANOND, Nattaya; CHITICHOTPANYA, Pisutsaran; NAKPATHOM, Monthon; MONGKHOLRATTANASIT, Rattanaphol (Journal of Metals, Materials and Minerals, 2022)
In recent years, the application of natural dyes in textile coloration has attracted significant study interest. In this current study, the bio-based dyeing of synthetic textile fiber, specifically acrylic yarn, with natural lac dye was investigated. The yarn was dyed using a meta-mordanting technique. The dyeing parameters, including temperature, time, pH of the dye bath, dye concentration, mordant type, and mordant concentration, were examined. Two eco-mordants, aluminium sulfate and ferrous sulfate, are compared against an eco-restricted copper sulfate in terms of color strength and fastness. The results demonstrated that the meta-mordanting technique can be used to dye acrylic fiber using natural lac dye. The optimum dyeing results were achieved using an acidic pH (2-3) and a temperature of 100℃ for 40 min of dyeing time. The color strength of the dyed samples was enhanced by the application of mordants. Color uniformity was achieved by controlling the temperature gradient in the Tg region. In terms of color change, the wash fastness properties of the dyed samples were found to be poor to moderate due to the dye’s susceptibility to alkaline washing. In terms of color fastness to rubbing and light, ferrous sulfate and copper sulfate produced superior results.